Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/lubricants10020015
|View full text |Cite
|
Sign up to set email alerts
|

History-Dependent Stress Relaxation of Liquids under High-Confinement: A Molecular Dynamics Study

Abstract: When liquids are confined into a nanometer-scale slit, the induced layering-like film structure allows the liquid to sustain non-isotropic stresses and thus be load-bearing. Such anisotropic characteristics of liquid under confinement arise naturally from the liquids’ wavenumber dependent compressibility, which does not need solidification to take place as a prerequisite. In other words, liquids under confinement can still retain fluidity with molecules being (sub-)diffusive. However, the extensively prolonged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Molecular dynamics (MD) simulation is a powerful tool which can be used to obtain microscopic insights into the properties of confined liquids behind the experimental results and to guide future research applications. Several studies have been conducted using both equilibrium and non-equilibrium MD simulations on confined liquids such as Lennard-Jones (LJ) particles [22][23][24] , water 11,14,25,26 , and hydrocarbons [27][28][29] . A recent simulation conducted by Ta et al 27 of a hexadecane film confined between iron oxide surfaces demonstrated that an increase in the shear rate can result in a decrease in the degree of ordering of the hexadecane film and an increase in the velocity slip at the solid-liquid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation is a powerful tool which can be used to obtain microscopic insights into the properties of confined liquids behind the experimental results and to guide future research applications. Several studies have been conducted using both equilibrium and non-equilibrium MD simulations on confined liquids such as Lennard-Jones (LJ) particles [22][23][24] , water 11,14,25,26 , and hydrocarbons [27][28][29] . A recent simulation conducted by Ta et al 27 of a hexadecane film confined between iron oxide surfaces demonstrated that an increase in the shear rate can result in a decrease in the degree of ordering of the hexadecane film and an increase in the velocity slip at the solid-liquid interfaces.…”
Section: Introductionmentioning
confidence: 99%